(3eSGQ GdTjYI aj GdJhGQjN GdTQYjI Yf GdGFeI GdegOjIs - (3eMeO Hf eMeO Hf GdfYeGf Hf YHO GdSdGe GdYcHQqj, CHh YHO Gddg, GdeajO, hjYQa HGHf GdeYde , J (B413 (3g`s ((3GdeZaQ Hf Ydi Hf efUhQ s)
(3ChdgG (B:s
(3bGd TjNfG GdMeO ddg Ydi eG HUQfG ef MceJg CeG HYO abO hbaJ GjOc Gddg Ydi eG PcQJ ef GdMGLI Edi eNJUQ ai JGQjN GjGe heSGQ GdTjYI hGYeGdge s
(3BNQgG (B:s
(3hQhi Gf ef Udi gPg GdUdGI ai djdI GdfUa ef TYHGf ZaQ Gddg SHMGfg PfhHg hbVi MhGFLg hGYW Shdg s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B21 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B306s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI WgQGf (B(2162) s
Keywords: (3GdJGQjNs